Protecting privacy in mandatory reporting of infectious diseases during the COVID-19 pandemic: perspectives from a developing country - SERT, GÜRKAN (BMJ PUBLISHING GROUP, 2021)
Mandatory reporting of infectious diseases (MRID) is an essential practice to prevent disease outbreaks. Disease notification is a mandatory procedure for most infectious diseases, even during non-pandemic periods in healthcare. The main rationale behind MRID is the protection of public health. The information and data provided by infectious disease reports are used for many purposes, such as preventing the spread and potential negative impact of infectious diseases, assessing the national and global situation regarding reported diseases, conducting scientific research and planning health policy. In this context, the relevant information benefits public health, health systems and scientific work. Additionally, the follow up and treatment of individuals with infectious diseases is a necessity in certain cases to protect those who cohabit with them. However, these benefits cannot be accepted as unrestricted justifications for MRID, since it is evident that reporting should be conducted within ethical and legal boundaries. MRID should only be devised and implemented with due regard to balancing potential benefits between all individuals, as well as between the individual and the rest of society. Disease notification systems that are not designed with a balancing and harm-reductionist approach may lead to stigmatisation and discrimination. This study aims to investigate the legal framework and ethical issues regarding the reporting of individuals diagnosed with COVID-19 in Turkey-which is a primary example of a developing country.
Keywords: confidentiality; privacy; COVID-19; informed consent; law; public law; ETHICS